2013
DOI: 10.3382/ps.2013-03159
|View full text |Cite
|
Sign up to set email alerts
|

Influence of monochromatic light on quality traits, nutritional, fatty acid, and amino acid profiles of broiler chicken meat

Abstract: The role of monochromatic lights was investigated on meat quality in 1-d-old straight-run broiler chicks (n = 360), divided into 6 light sources with 6 replicates having 10 chicks in each replicate. Six light sources were described as incandescent bulbs (IBL, as a control) and light-emitting diode (LED) light colors as white light (WL), blue light, red light (RL), green light, and yellow light. Among LED groups, the RL increased the concentration of monounsaturated fatty acids (P < 0.001), saturated fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
3
23
0
1
Order By: Relevance
“…In the present study, the MDA, the final product of lipid peroxidation, and PC, the product of protein oxidation, contents in muscle were quadratically decreased by L-theanine, which indicated a lower intramuscular oxidative damages. Consistent with these findings, the present study provided the first evidence in broilers that dietary L-theanine supplemen- (Franco, Rois, Vazquez, Purrinos, et al, 2012;Kim et al, 2013). Previous study reported that the AA profiles in serum, liver, and brain of rats could be changed by the administration of Ltheanine (Terashima, Takido, & Yokogoshi, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the MDA, the final product of lipid peroxidation, and PC, the product of protein oxidation, contents in muscle were quadratically decreased by L-theanine, which indicated a lower intramuscular oxidative damages. Consistent with these findings, the present study provided the first evidence in broilers that dietary L-theanine supplemen- (Franco, Rois, Vazquez, Purrinos, et al, 2012;Kim et al, 2013). Previous study reported that the AA profiles in serum, liver, and brain of rats could be changed by the administration of Ltheanine (Terashima, Takido, & Yokogoshi, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, for dual-purpose purebreds, environmental light and sexual maturity could be considered also for meat quality as these two factors could affect sensorial and chemical parameters of chicken meat (Touraille and Ricard, 1981;Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the total consumption of chicken meat has increased with the rapid development of the poultry industry 1,2 . Poultry meat generally contains not only nutrients but also enriches health‐promoting substances such as amino acids (AA) and n‐3 polyunsaturated fatty acids (PUFA) 3,4 . The characteristics of AA affect the umami and sweet flavor of meat 5 .…”
Section: Introductionmentioning
confidence: 99%